DEVELOPMENT OF ENGLISH LEARNING MEDIA FOR EARLY CHILDREN THROUGH ANDROID-BASED SONG MEDIA - Shafiyah, Shafiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Learning media are tools, facilities, or intermediaries used in the interaction process between the teacher and students to encourage the teaching and learning process to acquire knowledge. Skills strengthen what is being learned and help achieve quality learning goals. Engaging, effective, and modern interactive learning media based on Android is urgently needed to introduce the world of learning or material so that teachers and students know it. A teacher needs to keep up with the times. Now teachers must be creative and innovative in developing principles of integrating technology and learning activities; the development of the golden generation needs to be followed up by introducing English from an early age because English is an international language.The aims of this study are as follows (1) to describe the development of English language learning for early childhood education through Android-based song media and (2) to determine the effectiveness of English language learning media for early childhood education through Android-based song media.